Distributed photovoltaic power generation: Possibilities, benefits, and challenges for a widespread application in the Mexican residential sector - Pedro I. Hancevic; Hector M. Nu\~nez; Juan de Dios Enrique Rosellón Diáz (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Mexico plans to implement a national program to support the adoption of distributed photo-voltaic generation (DPVG) among qualified households. The main objectives of such a program would be to reduce the burden of the substantial federal energy subsidy and increase the share of renewable energy sources used to generate electricity. In this paper we assess the current conditions under which the Mexican residential electricity sector operates, and quantify the potential effects that the massive adoption of DPV systems would have on household expenditure and welfare, subsidy reduction, pollution and water resource usage. Based on the positive results in terms of both economic and environmental effects, our paper provides a significant support for further design and implementation of a DPVG program.
Keywords: Q28; Q42; Q53; 330; distributed solar photovoltaic generation; residential electricity consumption; energy subsidies; air pollution; water resource usage